Development Dilemma and Improvement Path of Elderly Education Governance under the Perspective of Multi-Source Stream Theory - Qi, Miao (Journal of Educational Research and Policies, 2025)
With the aging of the population, the importance of elderly education in improving the quality of life of the elderly has become increasingly prominent. This paper aims to explore the development dilemma of elderly education governance and its optimization path, in order to provide a reference for policy making. The study adopts a multi-source theoretical framework to analyze the challenges faced by elderly education governance. The results show that elderly education has problems such as uneven resource allocation, disconnection between educational content and demand, and lack of professional talents; unclear responsibilities of various departments and insufficient attention from local governments; policy implementation deviations, complex management systems and mechanisms, and insufficient financial investment. In response to these problems, this paper proposes optimization paths from the three perspectives, so as to promote the improvement of elderly education governance, promote the healthy development of elderly education, and help build an elderly-friendly society.